The Analysis of Consincing Money Deposits in The State Court As A Form of Accountability of Land Liberation Land Loading In Sumatera Toll Road In Kalianda State Court - Oksitania, Dilla Nandya; Erlina B; Yulia Hesti (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2021)
Land is the most important element for humans to live, this is because land is a place where natural and man-made resources grow and are also built. Indonesia even regulates land ownership through this Land Law so that land use or management can be carried out carefully in the present and in the future. Land issue is a problem that concerns the most basic rights of the people. If the person in possession of the receivable refuses payment from the debtor, then the party owed can make cash payment of the debt by offering a payment made by the bailiff accompanied by 2 (two) witnesses. If the debtor refuses to receive payment, the money is deposited in the cash registrar of the District Court as a deposit / consignment. The offer and safekeeping must be legalized by a judge's order. By carrying out a consignment, it will be freed from the obligation as the debtor, because a consignment can be equated with making payments. However, all this must be done in a manner regulated by statutory regulations. KThe signaling was carried out after the deliberation mechanism which was supposed to be a means of finding a middle way in determining the amount of compensation often failed to reach an agreement. the consignment was carried out so that government projects for the sake of continued progress Keywords: Consignment, Settlement of Land Acquisition Loss, Sumatran Toll Road